Intersecting squares: applied geometry in the architecture of Timurid Samarkand. Issue 2 (3rd July 2018) - Sakkal, Mamoun
ABSTRACT: This paper offers an overview of a collection of architectural patterns ornamented with Square Kufic inscriptions, focusing on the Bibi Khanum mosque built by Timur at the end of the fourteenth century in Samarkand. The paper discusses ways in which these repeating patterns may be seen as collections of adjacent and overlapping squares, several of which are original schemes that appear first in Timurid buildings. The paper details one of these schemes, Double Square, where two squares intersect on their diagonal axes. These patterns are presented as a system, rather than as individual designs, for the first time here. The intersecting square arrangements are uniquely appropriate for the rigid angularity of Square Kufic calligraphy; their patterns are a result of the practical application of script in architecture. They offer an exceptional union of calligraphy and geometry in the architectural arts of the Persianate world. GRAPHICAL ABSTRACT: